Modelling and simulation of extreme wave heights around agatti island of lakshadweep, west coast of India - Dinakaran, Shyamala Varthini; Alluri, Kiran Raju; Joseph, K Jossia; Murthy, M V Ramana; Venkatesan, Ramasamy (Frontiers in Built Environment, 2022)
Small islands experience variation in wave energy regime along shorter shoreline due to refraction, diffraction and variability in direction of wave travel. Nearshore Wave climate around these islands is quite complex due to wave transformation associated with configuration of islands, and high steepness in the bathymetry. Understanding wave energy will help in identifying suitable locations for coastal structures, wave energy devices and sediment budgeting. Assessment of extreme wave climate around the islands play a crucial role in the design and survival of coastal infrastructure for any developmental activities in islands. This study investigates the extreme wave climate around the Agatti island of Union Territory of Lakshadweep located in west coast of India. The spatial variability of wave energy distribution around the Agatti Island is analysed based on 10 years of wave hindcast data from spectral wave modelling for the period between 2011 and 2020 using Spectral Wave Model. In this study, third-generation spectral wave model is used to simulate the wave climate over the Arabian Sea. Regional Model was established using ECMWF model winds and the offshore wave parameters were validated with ocean observation AD07 deployed at water depth of 4020m in the Arabian Sea. To understand the nearshore wave transformation along the Agatti Island, local wave model of fine resolution was established using high resolution bathymetry and is validated using the coastal buoy (CB02) deployed near Agatti. Nearshore wave parameters such as Significant Wave Height (Hs), Peak Wave Period (Tp) and Mean wave direction (θm) were analysed. The wave power distribution around the island was quantified and demarcated for siting of offshore structures for developmental activities. The extreme wave heights for different return periods were estimated around the Agatti Island for design and analysis of coastal infrastructure.